THE INFLUENCE OF SERVICE ASSURANCE, EMPOWERMENT, RESPONSIVENESS IN SERVICE RECOVERY, AND WORK MOTIVATION ON CUSTOMER SATISFACTION THROUGH THE MEDIATING OF SERVICE QUALITY: Case Study at PT. Brantas Abipraya (Persero) - Aloysius Harry Mukti; Lalu Irjan Atmanegara (ESENSI: Jurnal Manajemen Bisnis, 2025)
The purpose of this research is to explore and analyze the influence of service assurance, empowerment, responsiveness in service recovery, and work motivation on customer satisfaction through the mediating role of service quality. This study was designed using a purposive sampling method with 320 respondents who are customers of PT Brantas Abipraya (Persero). Data were analyzed using the Structural Equation Model (SEM) with SmartPLS 4.0. The findings indicate that service assurance, empowerment, responsiveness in service recovery, and work motivation each have a positive influence on customer satisfaction. Furthermore, service quality successfully mediates the influence of service assurance, responsiveness in service recovery, and work motivation on customer satisfaction, but does not mediate the influence of empowerment on customer satisfaction.